Dark side of Electricity: Hospital based Retrospective Observation Study of Deaths Due to Electrocution (Indian Journal of Forensic Medicine & Toxicology, 2023)
Electricity is the set of physical phenomena associated with the presence and flow of electric charge. Electrical injuriesare a relatively common type of mechanical trauma that can be caused by lightning, low-voltage trauma, or high-voltagetrauma. They frequently have high morbidity and mortality rates. A hospital based descriptive observational study that wasconducted at the SMS Medical College, in the department of forensic medicine in Jaipur, Rajasthan from 20th June 2021 to19th June 2022. There were 75 death cases from electrocution that were included in the sample. Males made up 92% of cases,while females made up only 8% of cases, for a male to female ratio of 11.5 to 1. The majority of the subjects (34.67%) arebetween the ages of 21 and 30. Age group 31–40 (26.67%) came next. There are 54 (72% of the total) rural residents in thearea where the subject resides. The majority of the subjects, or 39 (52%), fell into the lower middle class according to theModified Kuppuswamy scale. Mortality rate in fatal electrocution cases can be reduced by providing immediate and adequateresuscitation. Although accidental electrocution accounts for the majority of fatalities, suicidal and homicidal electrocutionshould also be taken into account. In each of these situations, the incident’s history, along with a thorough investigation of thecrime scene and an autopsy report may enable us to determine the death’s cause and manner, allowing us to use the informationto plan and put into action preventive measures to lower the likelihood of future occurrences.
Keywords: Compensation, Electrocution, Modified kuppuswamy scale, Prevention, Resuscitation